The Place of Cyrillo-Methodian Heritage in the Christianization of Kievan Rus - Hetenyi, Martin (Communications - Scientific letters of the University of Zilina, 2017)
Constantine and Methodius laid important foundations for the diverse culture of Eastern Slavic peoples. In the spread of the ideals of this culture, Christianity played an important role. An official adoption of Christianity in A.D. 988 had several important features: development of art, craft, literature, sacral architecture, etc. It is thus understandable that in eastern Slavic countries, the cult of St. Constantine and Methodius began to grow immediately. However, there is a lack of information about the way the brothers‘ work affected Eastern Europe and the difficult journey it must have experienced. Both Slovak and Czech historiography provide only rough outlines of these matters. Researchers in Slovakia and the Czech Republic offer no detailed discussion of the huge contribution of Constantine and Methodius to the culture of Eastern Slavs. This condition may be the result of both limited source materials and limited access to the sporadically discovered materials.